Bacteria of the skin - Pyle, Charles A. (My University, 1904)
Introduction: The necessary requirements for the growth of bacteria being considered, it readily appealed to the writer that the surface of the human body furnished all of these necessary requirements. The excretions and exfoliated epithelium of the skin, the warmth of the body and protection from sunlight and fresh air by the clothing afford very favorable conditions for the growth of these organisms. To first find what bacteria are on the skin under varying conditions, their resistance to disinfectants and them determine their importance in surgical work and hygiene, this thesis is attempted.
Citation: Pyle, Charles A. Bacteria of the skin. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Bacteria; Skin; Dermotology; Theses